Application of concentrated learning technology in the professional training of forensic experts - D. V. Klymchuk; S. V. Ihnatov (Bulletin of Kharkiv National University of Internal Affairs)
The relevance of improving training to increase the productivity of experts in expert institutions has been emphasised. The world experience of applying concentrated learning in the general scientific process has been analysed. The structure of concentrated learning as a technology of the pedagogical process, as well as the resources that can be released to increase the productivity of learning through the use of concentrated learning technology, have been studied. The system of forensic experts’ training in Ukraine and the issues of professional training of forensic experts have been analysed and summarised. On the basis of the analysis, the features of application of the concentrated learning technology elements in the training and practical activities of forensic experts in Ukraine have been considered.